Effect of repeated epilation for minor trachomatous trichiasis on lash burden, phenotype and surgical management willingness: A cohort study. - Esmael Habtamu; Tariku Wondie; Wubshet Gobezie; Zerihun Tadesse; Bizuayehu Gashaw; Abebaw Gebeyehu; Chrissy H Roberts; E Kelly Callahan; David Macleod; Matthew J Burton (Public Library of Science (PLoS), 2020)
Background WHO endorsed the use of epilation as an alternative treatment to surgery for the management of both minor unoperated TT (UTT) and postoperative TT (PTT). However, some trachoma control programmes hesitated to implement epilation citing concerns that it would hamper TT surgical acceptance and result in larger numbers of and stiffer trichiatic eyelashes than the original TT lashes. We investigated the burden and phenotypes of post-epilation trichiatic eyelashes, and willingness to accept surgical management separately in unoperated and postoperative TT cases. Methodology/principal findings We recruited cases with minor (≤5 eyelashes from the upper eyelid touching the eye or evidence of epilation in <1/3rd of the upper eyelid) UTT (170) and PTT (169) from community-based screenings in Amhara Region, Ethiopia. Participants eyes were examined and data on present and future willingness to accept surgical management collected at baseline and every month for 6-months. Eyelashes touching the eye were counted and their phenotypes documented. Participants were trained on how to epilate. Epilation was done by the participants at home and by the examiner during follow-ups when requested by the participant. Follow-up rates were ≥97%. There was evidence of a significant reduction in the burden of trichiatic eyelashes in unoperated (mean difference = -0.90 [-1.11- -0.69]; RR = 0.50 [95% CI, 0.40-0.62]; p<0.0001), and postoperative (mean difference = -1.16 [-1.36- -0.95]; RR = 0.38 [95% CI, 0.31-0.48]; p<0.0001) cases 6-month after frequent epilation. Post-epilation trichiatic eyelashes at 6-months had higher odds of being thin (40.2% vs 55.8%, OR = 1.88 [95% CI, 1.21-2.93]; p = 0.0048), weak (39.8% vs 70.8%, OR = 3.68 [95%CI,2.30-5.88]; p<0.0001), and half-length (30.9% vs 43.3%, OR = 1.71 [1.09-2.68]; p = 0.020) than the pre-epilation trichiatic eyelashes in unoperated cases. There was a significant increase in the proportion of weak trichiatic eyelashes (OR = 1.99 [95% CI, 1.03-3.83; p = 0.039) in postoperative cases. In all 6 follow-up time points, 120/164 (73.2%) of unoperated and 134/163 (82.2%) of postoperative cases indicated that they would accept surgery if their trichiasis progressed. Conclusions/significance In this study setting, frequent epilation neither hampers surgical acceptance nor results in more damaging trichiatic eyelashes than the pre-epilation lashes; and can be used as an alternative to the programmatic management of minor unoperated and postoperative TT cases.